2008
DOI: 10.1021/es071945k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatile−Char Interaction on the NO Emission from Coal Combustion

Abstract: To clarify the effects of volatile-char interaction on the redistribution of fuel-N to N2 during devolatilization and the reduction of NO through gas-solid reactions during combustion, two types of experiments were performed on a novel reactor. The separate combustion of volatile and char and the combustion of entrained pulverized coal, and the formation of NO was examined between 800 and 1100 degrees C by using four typical Chinese coals with different ranks. The effect of volatile-char interaction on fuel-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Compared with the large amount of investigations on the reaction of NO and coal-char (Aarna and Suuberg, 1997;Johnsson, 1994;Li et al, 1998;Lu et al, 2009;Teng et al, 1992;Yamashita et al, 1993;Yao et al, 2008), researches on the interaction between NO and biomass char at high temperatures are limited. However, previous results have shown that there are still some obvious differences in the physicochemical characteristics and the reactivity of NO with biomass char and coal char (Dong et al, 2009b;Sahu et al, 2010;Vassilev et al, 2010;Wang et al, 2010a;Yin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the large amount of investigations on the reaction of NO and coal-char (Aarna and Suuberg, 1997;Johnsson, 1994;Li et al, 1998;Lu et al, 2009;Teng et al, 1992;Yamashita et al, 1993;Yao et al, 2008), researches on the interaction between NO and biomass char at high temperatures are limited. However, previous results have shown that there are still some obvious differences in the physicochemical characteristics and the reactivity of NO with biomass char and coal char (Dong et al, 2009b;Sahu et al, 2010;Vassilev et al, 2010;Wang et al, 2010a;Yin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The initial peak for NO formation was observed at around 330°C, due to the primary degradation of volatile-N. The second peak was focused around 580°C, resulting from the combustion of char-N (Yao et al, 2008). In order to better understand the formation of N species, the total FTIR integral values for all N species were correlated with the total N content of the raw ARs material, as shown in Fig.…”
Section: Key N-containing Species Release Characteristicsmentioning
confidence: 99%
“…The dried sludge has more ash and volatile content and lower calorific value than the coal, which is a disadvantage for the combustion purpose (Jayanti et al 2007;Yao et al 2008). To minimize the effect on CFB operation, 11.4 tons of sludge, equivalent to 5% of daily consumption of coal in CFB, was mixed with coal to incinerate.…”
Section: Reuse Of the Dried Sludge Granulesmentioning
confidence: 99%